2015
DOI: 10.1185/03007995.2015.1082995
|View full text |Cite
|
Sign up to set email alerts
|

Stroke associated with discontinuation of warfarin therapy for atrial fibrillation

Abstract: Warfarin discontinuation is associated with increased risk of ischemic stroke and TIA. Health care providers may need to take a more active role in the management of warfarin discontinuation and clinical outcomes, e.g., by considering newer anticoagulants with favorable risk-benefit profiles. Key limitations of the study include unavailability of important clinical factors and measures in claims data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 21 publications
1
26
0
2
Order By: Relevance
“…3538 Although overall adherence has not definitively been shown to be associated with stroke risk, gaps in therapy during treatment with warfarin has been shown to impart increased risk of stroke. 38 Gaps in therapy can include missed doses, as well as delays in filling subsequent prescriptions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3538 Although overall adherence has not definitively been shown to be associated with stroke risk, gaps in therapy during treatment with warfarin has been shown to impart increased risk of stroke. 38 Gaps in therapy can include missed doses, as well as delays in filling subsequent prescriptions.…”
Section: Discussionmentioning
confidence: 99%
“…3538 Although overall adherence has not definitively been shown to be associated with stroke risk, gaps in therapy during treatment with warfarin has been shown to impart increased risk of stroke. 38 Gaps in therapy can include missed doses, as well as delays in filling subsequent prescriptions. While individual missed doses could not be assessed in these data, we observed the number of gaps for each treatment group and showed that rivaroxaban was associated with fewer gaps compared with the other treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Although DOACs are easier to use than warfarin, poor medication compliance may have a negative impact on clinical outcomes [76].…”
Section: Dabigatran Compliancementioning
confidence: 99%
“…One-year persistence rate of warfarin is nearly 50% [78], although some authors report even smaller numbers [75,76]. However, contrasting results about this crucial issue have been published, demonstrating low compliance (namely \50%) also in patients treated with DE [79].…”
Section: Dabigatran Compliancementioning
confidence: 99%
“…Nasuprot tome, veće zadovoljstvo terapijom se izdvojilo kao multivarijantni prediktor niže verovatnoće nepovoljnih KV ishoda, odnosno ispitanici sa najvišom ocenom zadovoljstva sprovedenim lečenjem imali su upola nižu verovatnoću da dožive neki od nepovoljnih KV ishoda u udnosu na ispitanike sa najnižom ocenom. Moguće objašenjenje je da su bolesnici koji su bili zadovoljniji lečenjem ostvarili bolju terapijsku adherenciju i perzistenciju tokom narednih godinu dana, uključujući adekvatnu tromboprofilaksu, primenu antitrombocitnih i drugih KV lekova, što se povoljno odrazilo na sniženje rizika od komplikacija [27,28]. Takođe smo pokazali da je viši QoL multivarijantni prediktor nižeg rizika od simptomatske srčane slabosti, odnosno da ispitanici sa najvišim ukupnim AFEQT skorom imaju ~60% manju verovatnoću za ispoljavanje srčane insuficijencije od ispitanika sa najnižom ocenom QoL.…”
Section: Diskusijaunclassified